Paul, Phoebe, Timothy, and Their Collections for Judea - Fellows, Richard G. (2023)
Studies of Paul’s collection(s) for Judea have suffered from the largely unexamined assumption that he wanted all regions to donate at the same time. Paul and Phoebe collaborated to organize a collection from Rome, and Paul anticipated a collection from Asia. There was likely a collection from Galatia several years before the collection from Macedonia and Achaia, and there is little reason to doubt the collection from Antioch. The silence of Acts concerning these collections is no argument against them, and it can be explained as a protective measure. We have no evidence that any of the collections were rejected.
Keywords: Bibel. Apostelgeschichte, 20,3; Acts 20:3; Rom 15:30–31; Timothy; Phoebe; Paul; Collection